Kalesang Negeri Leahari Melalui Sosialisasi Pengelolaan Sampah dan Aksi Jaga Lingkungan - Laury M. Ch. Huwae; Jorgi B. Kurniawan; Ronald D. Hukubun; Sherly Lewerissa (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The lack of awareness of residents in Negeri Leahari to manage household waste and the non-functioning TPS3R (Reuse, Reduce and Recycle Waste Management Site) prompted the KKN team together with the PKM Unpatti Build Village team to offer a waste management program and protect the environment. The waste management program through environmental socialization activities and clean actions is carried out through several stages from location determination and review, preparation of work programs that include activities, waste education and its management, as well as environmental clean actions with the people of Negeri Leahari. The results of the work program include increasing knowledge about waste management and active participation of the local community in cleaning up the surrounding environment as a form of protecting the environment, starting from households to strategic locations in Leahari. In addition, this activity can help create a clean, comfortable, and healthy environment.